2015
DOI: 10.5194/acp-15-2159-2015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing turbulent parameters obtained from LITOS and radiosonde measurements

Abstract: Abstract. Stratospheric turbulence is important for the mixing of trace species and the energy balance, but direct measurements are sparse due to the required resolution and accuracy. Recently, turbulence parameters such as the energy dissipation rate ε were inferred from standard radiosonde data by means of a Thorpe analysis. To this end, layers with vertically decreasing potential temperature are analysed, which is expected to indicate turbulence. Such an application assumes a proportionality between the Tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…As noted in Bellenger et al (), considering that ε is linearly dependent on C K , the difference between C K = 0.3 and 1.0 changes ε by a factor of 3. On the other hand, several studies have shown that the value of C K appears over a wide range (Balsley et al, ; Fritts et al, ; Schneider et al, ). Schneider et al () estimated L T and L O on the same balloon from radiosonde and LITOS, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in Bellenger et al (), considering that ε is linearly dependent on C K , the difference between C K = 0.3 and 1.0 changes ε by a factor of 3. On the other hand, several studies have shown that the value of C K appears over a wide range (Balsley et al, ; Fritts et al, ; Schneider et al, ). Schneider et al () estimated L T and L O on the same balloon from radiosonde and LITOS, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several studies have shown that the value of C K appears over a wide range (Balsley et al, ; Fritts et al, ; Schneider et al, ). Schneider et al () estimated L T and L O on the same balloon from radiosonde and LITOS, respectively. From this estimation, C K was found to be widely distributed over 2 orders of magnitude.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of turbulence in atmospheric dynamics, a wealth of theoretical and experimental efforts has been carried out to identify the generation mechanisms, which are not fully quantified or understood (Wyngaard, 1992;Lübken, 1992Lübken, , 1997Müllemann et al, 2003;Rapp et al, 2004;Sharman et al, 2012;Schneider et al, 2015;Fritts et al, 2016, e.g.). According to the theory described above, turbulence is under the influence of shear and buoyancy forces, but not only of those.…”
Section: Discussionmentioning
confidence: 99%
“…Yagi and Yasuda, 2013;Mater et al, 2013). Some studies in the atmosphere also exist (Gavrilov et al, 2005;Wilson et al, 2014;Schneider et al, 2015). From the proportionality between L T and L O , one obtains for the determination of dissipation rates…”
Section: Derivation Of ε From Radiosonde Datamentioning
confidence: 99%
“…It is known that the ratio, however, has a large uncertainty (0.25–4), which leads to the uncertainty of ε with 2 orders of magnitude. Schneider et al () derived vertical profiles of ε with a balloon‐borne anemometer at a sampling rate of 8 kHz and compared them with estimates from the Thorpe analysis. They showed that the proportional coefficient had quite a broad range, whereas the most probable value of ( L O / L T ) 2 is 0.1.…”
Section: Introductionmentioning
confidence: 99%